Effects of Tempeh Probiotics on Elderly With Cognitive Impairment - Handajani, Yvonne Suzy; Turana, Yuda; Yogiara, Yogiara; Sugiyono, Sagita Pratiwi; Lamadong, Vincent; Widjaja, Nelly Tina; Christianto, Geovannie Audrey Moniqe; Suwanto, Antonius (Frontiers in Aging Neuroscience, 2022)
Studies have shown a strong relationship between the digestive system and the brain. Tempeh is a traditional Indonesian food rich in probiotics and beneficial for cognitive function. Probiotic supplement-based therapies that alter the composition of gut microbiota can help prevent cognitive decline. This experimental study involved a total of 93 subjects, divided into 3 groups : A, B and C/control (n: 34, 32, and 29), who were provided with probiotic supplementation isolated from tempeh for 12 weeks intervention. Inclusion criteria were age > 60 years, and memory impairment with the third repetition value of Word List Memory Immediate Recall (WLMIR) < 7. Subjects with diabetes were excluded. Cognitive function examinations were carried out before and after treatment. The tempeh-derived probiotics were prepared trough several processes. Lactic acid bacteria were isolated from tempeh, and a hemolysis test was carried out for an initial screening of the safety of bacterial isolates. Genomic isolation, detection of GABA-encoding genes, and species identification using the 16S-rRNA gene encoding were performed. A microencapsulation process was performed to produce two types of probiotic powders: group A probiotic powder containing 108 CFU/mL of probiotics and group B probiotics containing 107 CFU/mL of probiotics. Results: There was an increase in the cognitive domains of memory, learning process, and verbal fluency (p<0.05) in group A. Memory function, visuospatial, and verbal fluency improved in group B (p<0.05). Only an increase in the memory domain was observed in the control group. Improvement of the learning process occurred only in group A ( p = 0.006 ). The probiotics isolate used in the intervention was identified as Limosilactobacillus fermentum. We assigned this isolate as L. fermentum A2.8. The presence of the gene encoding GABA was found on this isolate. Conclusion: Administration of probiotics derived from L. fermentum at concentrations of 108 CFU/mL and 107 CFU/mL increased the cognitive domains of memory, language and visuospatial function. However, probiotic supplementation at a concentration of 108 CFU/mL was better in improving the learning process.